Prospective study of large uterine fibroids encountered during laparotomy and hysterectomy and their management - Nalini, Y. Lakshmi; Chandra, A. Sarath; Akshitha, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Study of large fibroids is necessary to throw light on complications associated with them. This helps the surgeon to safeguard patients from anticipated complications during surgery. The objective is to study the clinical features, complications and outcome of large uterine fibroids. Methods: A hospital based prospective study was carried out among 32 eligible patients undergoing laparotomy hysterectomy at Department of Obstetrics and Gynecology from October 2015 to June 2018. Age groups, clinical features, complications and outcome of surgery were recorded. Data was analyzed using proportions. Results: Majority of the study subjects were in the age group of 25-35 years. The most common presenting symptom of large size fibroid uterus was abnormal uterine bleeding followed by pain abdomen in 18.8% of the cases. Majority of the women had fibroid size of 16-20 weeks in 62.5% of the cases followed by size of the 20-26 weeks in 31.3% of the cases. Only two women had very large size of 26-28 weeks in 6.3% of the cases. Only three patients had intra operative complications (9.4%). Among them two (6.3%) had injury to the urinary bladder and only one had injury to the ureters. 90.6% of the cases had no intra operative complications. All cases had complete symptomatic relief. Thus the successful outcome was seen in 100% of the cases. Conclusions: Large uterine fibroids can end up with urological complications more than smaller fibroids. Among these bladder and ureteric complications are important. Malignant degeneration is rare. Other complications include infection and wound dehiscence.